Pengaruh Penyuluhan dengan Metode Ceramah Tentang Bahaya Rokok terhadap Perubahan Sikap Perokok Aktif - Rusmilawaty Rusmilawaty (Jurnal Vokasi Kesehatan, 2016)
Abstract: Influence of Counseling with Methods Lecture About The Dangers of Smoking Against Active Smokers Attitude Changes. The aim of this research is to determine the influence of counseling with methods lecture about the dangers of smoking against active smokers attitude changes in the Tirtajaya village in Bajuin Sub-district of Tanah Laut District at the year 2015. This research uses a type of research design, i.e. pre-experimental design with research structure one group pretest – post test design. The quantity of samples is 111 people. Results show that the active smokers attitude before given counseling about the dangers of smoking has score attitude amongst 23 to 42 with a grade average of 32,16, with the positive attitude as much as 44 respondents and negative attitude as much as 57 respondents. Active smokers attitude after being given Counseling about the dangers of smoking showing attitude scores between 32 to 52, with an average value of 41,74, and positive attitude as much as 53 respondents and negative attitude as much as 48 respondents. There is the influence of counseling with methods lecture about the dangers of smoking again stactive smokers attitude before and after the counseling gave with avalue of p=0,00.Abstrak: Pengaruh Penyuluhan Dengan Metode Ceramah Tentang Bahaya Rokok Terhadap Perubahan Sikap Perokok Aktif. Tujuan penelitian yaitu untuk mengetahui pengaruh penyuluhan dengan metode ceramah tentang bahaya rokok terhadap perubahan sikap perokok aktif di Desa Tirtajaya Kecamatan Bajuin Kabupaten Tanah Laut Tahun 2015. Penelitian ini merupakan penelitian pre-experimental design dengan rancangan penelitian one group pretest-post test design. Jumlah sampel 111 orang. Hasil penelitian menunjukkan bahwa sikap perokok aktif sebelum diberikan penyuluhan tentang bahaya rokok memiliki skor sikap antara 23 sampai 42 dengan nilai rata-rata 32,16, dengan sikap positif responden sebanyak 44 dan responden dengan sikap negatif sebanyak 57 orang. Sikap perokok aktif setelah diberikan penyuluhan tentang bahaya rokok memiliki skor sikap antara 32 sampai 52, dengan nilai rata-rata 41,74, dan sikap positif responden sebanyak 53 dan responden dengan sikap negatif sebanyak 48 orang.Ada pengaruh penyuluhan dengan metode ceramah tentang bahaya rokok terhadap sikap perokok aktif sebelum dan setelah diberikan penyuluhan dengan nilai P=0,00.